Mindfulness y regulación emocional en adolescentes: revisión integrativa - Quintana Asimbaya, Jenny Estefania (My University, 2025)
Over the past decade, mindfulness-based interventions have gained increasing relevance in addressing adolescent mental health. This study aimed to analyze the available scientific evidence on the effectiveness of mindfulness in emotional regulation among adolescents, through an integrative review of literature published between 2015 and 2025. International databases (PubMed, Scopus, PsycINFO, Web of Science) were consulted, including empirical, qualitative, and theoretical studies. Findings show that interventions implemented in school and clinical contexts improved attention, reduced emotional symptoms, and strengthened resilience. However, methodological limitations persist, such as small sample sizes, lack of active control groups, and limited longitudinal follow-up. It is concluded that mindfulness represents a promising strategy for adolescent emotional regulation, although greater methodological rigor and cultural adaptation are required for sustainable implementation in Latin America.
En los últimos diez años, las intervenciones basadas en mindfulness han adquirido relevancia en el abordaje de la salud mental adolescente. El presente estudio tuvo como objetivo analizar la evidencia científica disponible sobre la eficacia del mindfulness en la regulación emocional de adolescentes, mediante una revisión integrativa de literatura publicada entre 2015 y 2025. Se consultaron bases de datos internacionales (PubMed, Scopus, PsycINFO, Web of Science), incluyendo estudios empíricos, cualitativos y teóricos. Los resultados muestran que las intervenciones implementadas en contextos escolares y clínicos evidencian mejoras en la atención, la reducción de síntomas emocionales y el fortalecimiento de la resiliencia. Sin embargo, persisten limitaciones metodológicas como tamaños muestrales reducidos, ausencia de grupos de control activos y escaso seguimiento longitudinal. Se concluye que el mindfulness constituye una estrategia prometedora para la regulación emocional en adolescentes, aunque se requiere mayor rigor metodológico y adaptación cultural para su implementación sostenible en América Latina
Keywords: ADOLESCENCIA; APRENDIZAJE SOCIOEMOCIONAL; MINDFULNESS; SALUD MENTAL